2022
DOI: 10.1155/2022/4983532
|View full text |Cite
|
Sign up to set email alerts
|

A Lamin Family-Based Signature Predicts Prognosis and Immunotherapy Response in Hepatocellular Carcinoma

Abstract: Background. Lamin family members play crucial roles in promoting oncogenesis and cancer development. The values of lamin family in predicting prognosis and immunotherapy response remain largely unclarified. Our research is aimed at comprehensively estimating the clinical significance of lamin family in hepatocellular carcinoma and constructing a novel lamin family-based signature to predict prognosis and guide the precise immunotherapy. Methods. The expression features and prognostic value of LMNA, LMNB1, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…From in vitro and in vivo trials, miR-145modulated LMNB2 showed high expression in esophageal cancer, promoting migration and proliferation of esophageal cancer [32]. Furthermore, LMNB2 has the function of promoting migration, proliferation, and invasion in liver cancer [33] The signatures of LMNB1 and LMNB2 were reliable biomarkers for predicting the overall survival and immune treatment response of liver cancer [34].…”
Section: Discussionmentioning
confidence: 99%
“…From in vitro and in vivo trials, miR-145modulated LMNB2 showed high expression in esophageal cancer, promoting migration and proliferation of esophageal cancer [32]. Furthermore, LMNB2 has the function of promoting migration, proliferation, and invasion in liver cancer [33] The signatures of LMNB1 and LMNB2 were reliable biomarkers for predicting the overall survival and immune treatment response of liver cancer [34].…”
Section: Discussionmentioning
confidence: 99%